URGENSI TOLERANSI BERAGAMA DI INDONESIA - Kurniasih, Imas; Rohmatulloh, Rifqi; Al Ayyubi, Ibnu Imam (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
called tasamuh to anyone who has a different religion or belief, because differences are not something to be debated or a negative way that creates friction between groups or individuals. the urgency of tolerance can be a benchmark for seeing problems that occur in society in reviewing existing polemics so that religious, civilizational, and cultural tolerance in Indonesia can be seen, created, and maintained. The method used in this study is a descriptive qualitative research method with a literature study approach that refers to several research data sources and data collection techniques in the form of religious tolerance studies. The focus of the research that will be raised is the urgency of religious tolerance in Indonesia. The data collection technique used in this study was the library research method, namely library research and the data analysis technique used in this study was a descriptive method. In religion, every adherent is required to recognize the existence of the involvement of differences and similarities in creating harmony in the value of Unity in Diversity which is always echoed in Indonesia.